Strategi Pengelolaan Kelas yang Efektif untuk Meningkatkan Kedisiplinan Siswa SD - Lintang Rahma Putri (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
This article discusses effective classroom management strategies designed to enhance discipline among elementary school students. It emphasizes practical methods teachers can use to create a positive and structured learning environment , which in turn supports better student behavior and increased focus. The research utilized a mixed method approach, combining a systematic literature review (library research) with a qualitative case study at an elementary school. The case study involved observation, semi structured interviews with the principal, three high grade teachers, and 12 students, as well as documentation. Key findings indicate that effective strategies include flexible seating arrangements, mutually agreed upon class rules, positive reinforcement, and educative sanctions8. The study also highlights the significance of the teacher's consistency as a role model, positive communication, and student involvement in rule making9. Crucially, the research found that integrating a socio emotional and participatory approach, along with the active involvement of parents, provides a more substantial contribution to sustainable student discipline compared to rigid rule enforcement alone. The application of these strategies resulted in an average overall increase in student discipline of 21.25%. This approach not only reduces rule violations but also cultivates self discipline and responsibility, making the classroom atmosphere more conducive and productive